ALD Protection of Li‐Metal Anode Surfaces – Quantifying and Preventing Chemical and Electrochemical Corrosion in Organic Solvent. Issue 21 (24th August 2016) - Lin, Chuan‐Fu; Kozen, Alexander C.; Noked, Malachi; Liu, Chanyuan; Rubloff, Gary W.
Abstract : Chemical and electrochemical instability of the Li metal interface with organic solvent has been a major impediment to use of Li‐metal anodes for next‐generation batteries. Here the character of Li surface degradation and the application of atomic layer deposition (ALD) as a protection layer to suppress the degradation are addressed. Using standard Li foil samples in organic solvent with and without in situ deposited ALD Al2 O3 protective layers, results from in situ atomic force microscopy, mass spectrometry (including differential electrochemical mass spectrometry), X‐ray Photoelectron Spectroscopy (XPS), and ex situ scanning electron microscopy/energy dispersive X‐ray spectroscopy are reported. Despite the presence of a thin oxide/hydroxide/carbonate layer on the Li foil surface, degradation readily occurs in organic solvent, particularly at surface features such as ridges. Introduction of the ALD protective layer – deposited directly on this Li foil surface – dramatically suppresses the degradation. Abstract : The effects of native oxide layer and additional thin atomic layer deposition protection layer on Li‐metal foils are investigated. We identify and quantify the solvent decomposition, and solid electrolyte interphase formation through in‐situ atomic force microscopy and mass spectrometry, and reveal that the introduction of the ALD protective layer suppresses the degradation/solvent decomposition and improves the Li‐metal/solvent interfacial stability.